Analisis Transparansi Pengadaan Barang dan Jasa di Lingkungan Pemerintah - Siburian, Gunawan Syahputra; Rizki, Nurul Aulia; Zebua, Nofatrio Soarota; Miswanda M, Tantra; Elmilawaty, Novi; Siregar, Oktarini Khamilah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Procurement of goods and services within the government is a crucial process in effective public financial management. Transparency in procurement is an important aspect to ensure accountability, reduce the risk of corruption, and increase the efficient use of public budgets. This research reviews literature related to the analysis of transparency in the procurement of goods and services within the government. The review includes identifying key challenges such as corruption, lack of access to information, and organizational cultural barriers, as well as proposed solutions such as strengthening regulations, increasing the use of information technology, and civil society participation in oversight. The results of this research provide an in-depth understanding of the complexity and importance of transparency in the context of procurement of goods and services in government, with the hope of providing guidance for better policies and practices in the future.